Properties of biologically relevant solution mixtures by theory and simulation - Dai, Shu (Kansas State University, 2014)
Molecular Dynamics (MD) simulations have played an important role in providing detailed atomic information for the study of biological systems. The quality of an MD simulation depends on both the degree of sampling and the accuracy of force field. Kirkwood-Buff (KB) theory provides a relationship between species distributions from simulation results and thermodynamic properties from experiments. Recently, it has been used to develop new, hopefully improved, force fields and to study preferential interactions. Here we combine KB theory and MD simulations to study a variety of intermolecular interactions in solution. Firstly, we present a force field for neutral amines and carboxylic acids. The parameters were developed to reproduce the composition dependent KB integrals obtained from an analysis of the experimental data, allowing for accurate descriptions of activities involved with uncharged N-terminus and lysine residues, as well as the protonated states for the C-terminus and both aspartic and glutamic acids. Secondly, the KB force fields and KB theory are used to investigate the urea cosolvent effect on peptide aggregation behavior by molecular dynamics simulation. Neo-pentane, benzene, glycine and methanol are selected to represent different characteristics of proteins. The chemical potential derivatives with respect to the cosolvent concentrations are calculated and analyzed, and the four solutes exhibit large differences. Finally, the contributions from the vibrational partition function to the total free energy and enthalpy changes are investigated for several systems and processes including: the enthalpy of evaporation, the free energy of solvation, the activity of a solute in solution, protein folding, and the enthalpy of mixing. The vibrational frequencies of N-methylacetamide, acetone and water are calculated using density functional theory and MD simulations. We argue that the contributions from the vibrational partition function are large and in classical force fields these contributions should be implicitly included by the use of effective intermolecular interactions.
Keywords: Molecular dynamics simulation; Force field; Preferential interaction; Vibrational partition function; Chemistry (0485)